Electrocardiographic Changes Of Labrador Dogs With Age - Mohapatra, Swagat; Mahapatra, A.P.K.; Pradhan, S.R.; Kundu , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study of electrocardiographic changes of Labrador dogs with age was performed which showed that the P amplitude of older dogs was significantly higher than P amplitude of younger dogs. The Q wave amplitude was found to be decreasing with the advancement of age . QRS complex and R-R were significantly higher in group 2 dogs that group 1 dogs. Highest heart rate was recorded in group 1 dogs. Pulse rate of group 2 dogs was significantly higher as compared to group 1,3,and 4 dogs.